Bad Smells in Software Product Lines: A Systematic Review - Vale, Gustavo; Figueiredo, Eduardo; Abílio, Ramon; Costa, Heitor (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2014: Anais do VIII Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2014)
Software product line (SPL) is a set of software systems that share a common, managed set of features satisfying the specific needs of a particular market segment. Bad smells are symptoms that something may be wrong in system design. Bad smells in SPL are a relative new topic and need to be explored. This paper performed a Systematic Literature Review (SLR) to find and classify published work about bad smells in SPLs and their respective refactoring methods. Based on 18 relevant papers found in the SLR, we identified 70 bad smells and 95 refactoring methods related to them. The main contribution of this paper is a catalogue of bad smells and refactoring methods related to SPL.